Evaluation of the use, storage, and administration of narcotic drugs in pharmacies, hospitals, and community health centers: A literature review - Maryono, Khaliq; Hermansyah, Andi; Wijaya, I Nyoman (Science Center Group, 2025)
Background: The management of narcotic drugs in healthcare facilities requires strict control because these medicines have significant therapeutic benefits while also posing a high potential for misuse. Inappropriate practices in narcotic drug use, storage, and administration may increase the risk of medication errors and regulatory violations. Objective: This study aimed to evaluate the use, storage, and administration of narcotic drugs in pharmacies, hospitals, and community health centers through a comprehensive literature review. Methods: This study employed a systematic literature review design following the PRISMA 2020 guideline recommended by the EQUATOR Network. Literature searches were conducted in the Google Scholar database using keywords related to the evaluation of narcotic drug use, storage, and administration in healthcare facilities. Articles published between 2020 and 2024 were screened based on predefined inclusion and exclusion criteria. From 236 identified records, 21 articles met the eligibility criteria and were analyzed using a thematic synthesis approach. Results:The review showed that narcotic drug use in pharmacies was predominantly associated with codeine-containing preparations, whereas hospitals maintained a broader range of narcotic drugs including fentanyl, morphine, and pethidine. Community health centers mainly utilized methadone as part of methadone maintenance therapy programs. Storage compliance was generally high in pharmacies, while hospitals showed moderate variation and community health centers demonstrated more limitations in storage infrastructure. Administrative compliance was generally adequate, although several studies reported incomplete documentation of physician and patient information. Conclusion: Narcotic drug management across healthcare facilities is generally implemented according to regulatory standards, although variations in compliance remain in terms of use, storage, and administrative procedures. Strengthening monitoring systems, improving pharmaceutical workforce capacity, and ensuring consistent implementation of standard operating procedures are necessary to enhance the safety and accountability of narcotic drug management.